Meta-Analisis Validitas dan Praktikalitas Lembar Kerja Peserta Didik Berorientasi Problem Based Learning untuk Peserta Didik Fase E SMA/MA - Amanda, Bella; Zulyusri, Zulyusri (YASIN, 2025)
The 2013 Curriculum emphasizes the importance of active student engagement in the learning process, requiring the implementation of instructional models that promote participation and independent problem-solving. One such relevant model is Problem Based Learning (PBL). This study is a meta-analysis aimed at examining the validity and practicality levels of PBL-based Student Worksheets (LKPD) as a medium for biology instruction. Data were collected from 10 articles published between 2021 and 2024 in various reputable journals. Data collection was conducted through document review, and analysis was carried out using an average percentage formula. The results show that PBL-based LKPD has a validity level of 93.10% and a practicality level of 92.20%, both of which fall into the very valid and very practical categories. These findings indicate that PBL-based LKPD can serve as an effective and engaging learning medium, supporting students’ competency achievement. The conclusion of this study is that PBL-based LKPD is suitable for use in biology instruction in alignment with the demands of the 2013 Curriculum. The implications of this research include reinforcing the literature on problem-based learning media and offering practical recommendations for educators and instructional material developers. This study also opens opportunities for further research to evaluate the effectiveness of PBL-based LKPD implementation in broader educational contexts and across different subjects.